“Shot to the Heart”: Case Report and Concise Review of Cardiac Gunshot Injury - Kawall, Tiffany (J Investig Med High Impact Case Rep, 2020)
Penetrative cardiac injury can often result in life-threatening sequelae such as myocardial contusion or rupture, coronary vessel and valvular damage, pericardial effusion with tamponade, and arrhythmias of which gunshot injury is a chief culprit. We report a case of a suspected acute coronary syndrome after a cardiac gunshot injury that was conservatively managed.